New Insight into the Pathogenesis of Erythema Nodosum Leprosum: The Role of Activated Memory T-Cells - Negera, Edessa; Bobosha, Kidist; Walker, Stephen L.; Endale, Birtukan; Howe, Rawleigh; Aseffa, Abraham; Dockrell, Hazel M.; Lockwood, Diana N. (Frontiers in Immunology, 2017)
Memory T-cells, particularly, effector memory T cells are implicated in the pathogenesis of inflammatory diseases and may contribute to tissue injury and disease progression. Although Erythema Nodosum Leprosum (ENL) is an inflammatory complication of leprosy, the role of memory T cell subsets has never been studied in this patient group. This study was aimed at investigating the kinetics of memory T cell subsets in patients with ENL before and after predninsolone treatment. A case-control study design was used to recruit 35 untreated patients with ENL and 25 non-reactional lepromatous leprosy (LL) patient controls at ALERT Hospital, Ethiopia. Venous blood samples were obtained before, during and after treatment from each patient. Peripheral blood mononuclear cells (PBMCs) were isolated and used for immunophenotyping of T cell activation and memory T-cell subsets by flow cytometry. The kinetics of these immune cells in patients with ENL before and after treatment were compared with LL patient controls as well as within ENL cases at different time points. The median percentage of CD3+, CD4+ and CD8+ T-cells expressing activated T-cells were significantly higher in the PBMCs from patients with ENL than from LL patient controls before treatment. The median percentage of central and activated memory T-cells were significantly increased in patients with ENL compared to LL patient controls before treatment. Interestingly, patients with ENL had a lower percentage of naïve T cells (27.7%) compared to LL patient controls (59.5%) (P<0.0001) before treatment. However, after predninsolone treatment, patients with ENL had a higher median percentage of naïve T-cells (43.0%) than LL controls (33.0%) (P<0.001). The median percentage of activated T-cells (effector memory and effector T-cells) was significantly increased in patients with ENL (59.2%) before treatment compared to after treatment with predninsolone (33.9%) (P<0.005). This is the first work which has shown T-cell activation and the different subsets of memory T cells in untreated patients with ENL. Consequently, this study delineates the role of T-cell activation in the pathogenesis of ENL reaction and challenges the long-standing dogma of immune-complex as a sole etiology of ENL reaction.